HUBUNGAN ANTARA KEMANDIRIAN BELAJAR DENGAN DISIPLIN SISWA - Rini Mulyani; Tatang Muhajang (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2020)
THE CORRELATION BETWEEN STUDENT’S LEARNING INDEPENDENCE AND STUDENT’S DISCIPLINE.This research is correlation study research that using quantitative approach is done in students’ grade of Fifth on Elementary School Pondok Rumput 1 Bogor city with amount 102 students as population. The samples are collected by simple random sampling technique which amount of samples from formula calculate are 51 students. The aim of this research is to know correlation between student’s learning independence and student’s discipline. The data of this research is collected with using questionnaire Likert scale for independence to discipline student’s..Validityof the instrument from learning independence and student’s discipline is calculated by using Product Moment Pearson formula and for reliability is calculated by using Alpha Cronbach formula. The population of this research is collected with using Taro Yamane formula with 10% precision. This quantitative research is conducted with pre validity and reliability instrument which next to survey the samples to get valid and reliable. After that, the result of this research is showed that has correlation between learning independence and student’s discipline, it is showed with statistical analysis that producing regression coefficient score (rxy) amount 0,99 and got t-calculateis 49,14. It is showed that has correlation between learning independence and student’s discipline, while determination coefficient (r2) is 0,98 or 98%. It means that score of learning discipline 98% is based on learning independence, with regression equality Y = 13,16 + 0,99X, is significance, so each increasing1 unit independence will improve student slearning discipline for 0,99 unit. Accordingto the result above, it can be concluded that has correlatiton betwen student’s learning independence and students learning discipline. It is showed that for improving learning discipline has to fix that learningindependence.